(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Poland syndrome is a rare congenital condition characterized by unilateral absence or underdevelopment of the pectoralis major muscle, often combined with upper limb anomalies. This study evaluates reconstructive chest surgery outcomes in children with Poland syndrome, focusing on functional recovery, cosmetic results, and postoperative complications. A retrospective analysis of 28 pediatric patients treated between 2015 and 2023 was conducted. Surgical reconstruction was performed using autologous tissue flaps, silicone implants, and muscle transposition techniques. The results demonstrate that individualized reconstructive approaches significantly improve thoracic symmetry and upper limb functionality, with minimal complication rates.